Mechanical, thermal, and structural properties of uniaxially drawn polylactic acid/halloysite nanocomposites. Issue 38 (15th February 2020) - Bagheri, Ehsan; Mosaddegh, Peiman; Behzad, Tayebeh
Abstract: The effect of solid‐state drawing at different conditions including drawing ratio (DR), drawing temperature (DT), and drawing speed (DS) on mechanical, thermal, and structural properties of polylactic acid (PLA)/halloysite nanotubes (HNTs) composites were studied. PLA/HNTs composite films were prepared by melt mixing process followed by compression molding. Subsequently, drawing was performed using a tensile testing machine. Field emission scanning electron microscopy confirmed alignment and orientation of polymer chains and HNTs after stretching. Thermal and mechanical analysis of the drawn films revealed that glass transition temperature, crystallinity, ultimate tensile strength, and Young's modulus were enhanced by increasing DR, DT, and DS. However, toughness was decreased by increasing DR and DS and increased by increasing DT. In addition, the drawn nanocomposites showed superior mechanical and thermal properties compared to the drawn neat PLA films indicating the high efficiency of solid‐state drawing and positive effect of HNTs. Therefore, this study could be helpful to introduce an approach to enhance the properties of biopolymers and renewable polymers by uniaxial drawing. Abstract : Polylactic acid (PLA)/halloysite nanotubes (HNTs) composites were drawn at different ratios, temperatures, and speeds. PLA chains and HNTs were oriented in the stretching direction and the dispersion of HNTs was enhanced for the drawn sample. As a result, mechanical and thermal properties were enhanced significantly after drawing.